A novel retrieval algorithm of multi-longitudinal-mode high-spectral- resolution lidar based on complex degree of coherence and the analyses of absolute errors. (September 2021) - Gao, Fei; Chen, Ting; Chen, Kaijun; Zhang, Rui; Wang, Li; Liu, Jingjing; Hua, Dengxin; Stanič, Samo
Highlights: Thegeneralretrievalequationsof aerosol optical properties using high-spectral-resolution lidarare deduced, which shows the effective transmittance of optical discriminator is the most important parameter in data retrieval. A novel retrieval algorithm of aerosol optical properties using the multi-longitudinal-mode pulsed high-spectral-resolution lidar is presented, which is a function of complex coherence degreeand verified the correctness. The absolute errors of the measurements of aerosol backscattering coefficient and optical depthusing the multi-longitudinal-mode high-spectral-resolution lidarare analyzed from the systematic effect and random effect, which shows that the absoluteerror of aerosol optical backscattering coefficient can be ignored and the absolute error of optical depth can be controlled within 0.4 in the majority of the lidar data when the relative error of δ is within 20%. Thepreliminary experiments of the constructed multi-longitudinal-mode high-spectral-resolutionlidar areperformed.The retrieved results of aerosoloptical properties using the multi-longitudinal-mode high-spectral-resolutionlidarhas proven that the multi-longitudinal-mode high-spectral-resolutionlidarhasthe capability in the fine detection of aerosol optical properties. Abstract: Multi-longitudinal-mode (MLM) high-spectral-resolution lidar (HSRL) selects an optical interferometer with the periodic transmittance function as the spectral discriminator to separate aerosol Mie scattering signals and molecular Rayleigh scattering signals excited by the MLM pulsed lasers, such as Mach-Zehnder interferometer, Michelson interferometer, Fabry-Perot etalon and so on. In this paper, we deduce a novel algorithm for retrieving aerosol backscattering coefficient, optical depth, and aerosol extinction coefficient in the application of the MLM HSRL, in which the lidar returns should be considered as a quasi-monochromatic light. Under such a condition, the effective transmittance of Mach-Zehnder interferometer is a function of the complex degree of coherence, which plays an important role in the retrieval algorithms of aerosol optical properties. The retrieval algorithms of aerosol backscattering coefficient, optical depth and aerosol extinction coefficient based on the complex degree of coherence are presented in detail and their correctness is verified by the system simulation using an experimental Mie-Rayleigh lidar returns. Meanwhile, the absolute errors of the measurements of aerosol backscattering coefficient and optical depth are analyzed from the systematic errors and random errors. The simulation results show that the presence of aerosol layers or cloud layer deteriorates considerably the accuracy of the retrieved aerosol backscattering coefficient and optical depth, and the total absolute error of aerosol backscattering coefficient is ignored, as well as the total absolute error of optical depth can be controlled within 0.4 in the majority of the lidar data when the relative error of δ is within 20%. Both measurement examples and continuous observations from the constructed MLM HSRL have proven that the MLM HSRL has the capability in the application of fine detection of aerosol optical properties.